Preliminary characterization of corn cob ash as an alternative material for ceramic hollow fiber membrane (CHFM/CCA) - Kamarudin, Noor Hasliza; Harun, Zawati; Othman, Mohd Hafiz Dzarfan; Hubadillah, Siti Khadijah; Yusof, Khairul Nazri; Jamaluddin, M.R. (Materials and Energy Research Center, 2018)
Currently, exchanging trends in the expensive usage of ceramic materials such as alumina, zirconia etc. into economical ceramic raw sources have been extensively studied over the last decade for various technological applications. Despite the fact that this ceramic compound or elements offer a great performance and stability, especially at high temperature, the basic commercial price and higher sintering temperature of this compound which is a little bit higher have hindered the used of these materials. Thus interest in fabricating of bio-ceramic membrane using corn cob ash (CCA), an agricultural by product not only offered the development of new low cost materials but also able to enhance better properties and performance. The suitability of corn cob ash as an alternative material for ceramic hollow fiber membrane fabrication (CHFM/CCA) as a main substrate was investigated via combined phase inversion and sintering technique based on several controlled operating parameters. The effects of selected bore fluid (5, 10, 15 and 20 mL/min) and different sintering temperature (800 °C, 900 °C, 1000 °C, 1100 °C) towards membrane structure and properties were observed and studied. Interestingly, characterization analysis of the SEM morphology showed that the potential of the main constituents of corn cob ash which highly consisted of silica, alumina and calcium oxide are able to improve the properties of CHFM/CCA by lowering sintering temperature (1000 °C) as compared to the standard CHFM bodies which normally has sintering temperature higher than 1200 °C. Thus, the use of corn cob ash not only able to enhance ceramic properties but also able to reduce sintering temperature. Reduction in energy consumption with slightly reduced sintering temperature also will offer a better sustainable process through recycling abundant waste materials as well as emphasis on the green resources. With that respect, the bio-material of corn cob ash is capable to replace the commercial ceramic membrane materials for membrane applications by considering the availability of this agro waste product as the main crops in most countries in the world.